A COMPARATIVE STUDY ON CHARACTERIZATION OF PROCESSED AND UNPROCESSED SORGHUM FLOURS - S.M. DEVATHA (The Journal of Research ANGRAU, 2024)
The effect of physical, technological and functional properties of unprocessed, germinated and dry roasted grains and flours of sorghum were studied in the year 2023. The physical properties of the grains such as length, breadth, length/breadth ratio, thousand grain weight showed that, germinated grains measured minimal results as the stores were utilized for sprouting. Germinated sorghum yielded 94.6%, whereas, unprocessed and roasted yielded 91% of the total flour yield. The technological properties of the flours were analyzed as quality indicator. Bulk density, oil and water holding capacity, and swelling capacity of the roasted flour were higher in quality when compared to unprocessed flour. Optical property indicated that roasted flour was darker and germinated sorghum flour was lighter than unprocessed flour. FTIR of germinated sorghum flour showed stronger peaks indicating the presence of polysaccharides. TGA of germinated sorghum flour exhibited maximum reaction zone due to changes in saccharides and dextrin. Roasted sorghum flour showed better properties that increase hardness, whereas, germinated flour soften the food product. Sorghum flour showed less than 7 x 10-1 CFU/g at day 180.